Propuesta metodológica para identificación de atractivos turísticos en el cantón Chaguarpamba, provincia de Loja, utilizando geo información. - Abrigo Ochoa, Karen Lizbeth (2022)
The present research was carried out in the Chaguarpamba canton located in the province of Loja, 3 objectives were proposed for the fulfillment of each of them, methodological processes were established from the selection of variables, the correct download of their Shapefile in the free access database data and their due application in the ArcGIS software, the realization of thematic maps for their respective analysis, finally the elaboration of a base model sheet with variables established by GIS analysis and field corroboration, the file contains variables, sub variables, evaluation criteria, weighting and levels of hierarchies defined by bibliographic supports. For the application of the methodological proposal elaborated, the 31 attractions of the Chaguarpamba canton were submitted by the elaborated file of the methodological proposal and by the file of the current methodology of the MINTUR, with the results of their weightings was compared through a matrix where the success of the research was verified. The filling of the sheets and the verification of the results were carried out successfully thanks to the field visit previously carried out. Through the interview technique, the current state of the Chaguarpamba canton was diagnosed in terms of its promotion and dissemination, in order to later carry out the approach of the strategy that strengthens tourism in the canton. The results start from the elaboration of a new survey and hierarchy of tourist attractions with 9 established variables, 4 of them by analysis of geographic information systems and the remaining 5 complementary by field verification with a general total of 41.70 points that refers to an attraction that is fully equipped, with accessibility and infrastructure; to define the level of hierarchies he used this total by dividing it for the number of hierarchies, where he threw as a rank less than 8.34 – 0, establishing the levels from Hierarchy IV to Resource. To verify the success of the research, both proposals were applied to the 31 tourist attractions of the Chaguarpamba canton, in the case of applying the MINTUR methodology all the attractions have a hierarchy II instead when applying the methodological proposal elaborated, 20 of them reach Hierarchy I and the remaining 10 in Resource, 1 of them was not valued due to their current conditions (temporary closure of the establishment). When the field visit was carried out, it was found that the results of the methodological proposal are more subject to reality than those of MINTUR, being positive results for the research. Finally, for the promotion and dissemination of tourist attractions based on the interview conducted, tourist maps were prepared for each of the parishes and in general of the entire Chaguarpamba canton for the strengthening of tourism in physical and digital media in this canton. Keywords: tourist attraction, methodological proposal, GIS and tourism, tourist variables, Chaguarpamba canton.